The Development of Palestinian Archeology as a Discipline - Toombs, Lawrence E. 1919-2007 (1982)
By focusing on what is distinctive of archeology, namely its excavation method, and not on its relationship to other disciplines such as biblical studies, linguistics, and history, a clearer definition of archeology as a discipline can be achieved. On the basis of this assumption, three major themes that characterize the development of Palestinian archeology since the late 1800s are isolated: the intention of the excavators, the field methodology, and the type of data gathered. Refinements in each of these concerns have shaped the evolution of Palestinian archeology and created the dilemmas with which the modern excavator must cope.